Surveillance and Genomic Analysis of Third-Generation Cephalosporin-Resistant and Carbapenem-Resistant Klebsiella pneumoniae Complex in Germany - Kyriaki Xanthopoulou; Can Imirzalioglu; Sarah V. Walker; Michael Behnke; Ariane G. Dinkelacker; Simone Eisenbeis; Petra Gastmeier; Hanna Gölz; Nadja Käding; Winfried V. Kern; Axel Kola; Evelyn Kramme; et al. (MDPI AG, 2022)
To analyse the epidemiology and population structure of third-generation cephalosporin-resistant (3GCR) and carbapenem-resistant (CR) Klebsiella pneumoniae complex isolates, patients were screened for rectal colonisation with 3GCR/CR K. pneumoniae complex on admission to six German university hospitals (2016-2019). Also collected were 3GCR/CR and susceptible K. pneumoniae isolates from patients with bloodstream infections (2016-2018). Whole-genome sequencing was performed followed by multilocus sequencing typing (MLST), core-genome MLST, and resistome and virulome analysis. The admission prevalence of 3GCR K. pneumoniae complex isolates during the 4-year study period was 0.8%, and 1.0 bloodstream infection per 1000 patient admissions was caused by K. pneumoniae complex (3GCR prevalence, 15.1%). A total of seven K. pneumoniae complex bloodstream isolates were CR (0.8%). The majority of colonising and bloodstream 3GCR isolates were identified as K. pneumoniae, 96.7% and 98.8%, respectively; the remainder were K. variicola and K. quasipneumoniae. cgMLST showed a polyclonal population of colonising and bloodstream isolates, which was also reflected by MLST and virulome analysis. CTX-M-15 was the most prevalent extended-spectrum beta-lactamase, and 29.7% of the colonising and 48.8% of the bloodstream isolates were high-risk clones. The present study provides an insight into the polyclonal 3GCR K. pneumoniae population in German hospitals.